Validitas dan Praktikalitas Modul Titrasi Asam dan Basa Berbasis Inkuiri Terbimbing dilengkapi Soal-Soal Tipe HOTS - Eka Frima Asda; Iryani Iryani (Universitas Negeri Padang, 2020)
This study aims to determine the validity and practicality categories of the modules that have been produced. This type of research is classified as a Plomp model which has three stages, preliminary research, prototype formation and assessment. The instruments used were validation and practicality sheets in the form of questionnaire sheets. The products produced were tested by 5 validators consisting of 2 chemistry majors at FMIPA UNP and 3 teachers from MAN 2 Pesisir Selatan and practicality tests conducted by 2 chemistry teachers and 30 students of class XI MIPA MAN 2 Pesisir Selatan. Based on the validation results obtained kappa moment value (k) of 0.87, then the practicality of the teacher and practicality of students obtained an average value of kappa moments (k) of 0.85 and 0.91. The value obtained shows that the module produced is very valid and practical.